Regulating pressing systemic risks: But not too soon? - Defne Halil; Konrad Kollnig; Aurelia Tamò-Larrieux (Internet Policy Review, 2025)
Online platforms have transformed how we live. This has raised concerns around how such platforms impact citizens' constitutionally-protected rights and freedoms, such as the freedom of expression and information, right to privacy, and protection from discrimination. To hold online platforms to account, researchers need access to platform data but this has proved to be difficult in the past. In response, the EU's 2022 Digital Services Act (DSA) imposes explicit obligations on very large online platforms (VLOPs) and very large online search engines (VLOSEs) to provide "vetted researchers" with necessary data to study systemic risks facilitated by these platforms. In this paper, we analyse how the platform data access provisions of the DSA work in practice and show the results of 27 data access requests launched across all EU member states. The results show that while the willingness of policymakers to address systemic risks on platforms is clearly present, we are not yet able to obtain meaningful data for research. In fact, the process of ensuring such access has been repeatedly delayed by the responsible authorities. For example, one authority claimed that requests not written in its national language would violate its country's procedural law and were thus not admissible. This is arguably not in line with the urgency required to address prevalent systemic risks, especially in a pivotal election year like 2024, the year when the study was conducted.
Keywords: 300; Digital Services Act (DSA); Data access requests; Digital services coordinators